Modelo de gerenciamento dos serviços de distribuição física numa agroindústria - Rocha, Jiane Toller da (2006)
In a globalized and competitive world, logistics is receiving a lot of attention from business managers because of its importance concerning the fidelity of customers and their participation in the total costs of the company. Therefore, this paper aims to develop a model to the management of the services of physical distribution based on the six sigma strategy in an agroindustry that produces canola oil and it is located in the northwest of the state of Rio Grande do Sul, Brazil. The data were collected by using a questionnaire which refers to the level of satisfaction and the importance of the services offered by the company concerning the customers attendance; the kind of ordering, invoice service and payment; logistic of transports and the information given. In order to analyze the data it was used the descriptive statistics and the techniques of analyses Cluster hierarchic and Cluster k-means. The six customers who buy unmanufactured canola oil from this company took part on this study. The results showed that the customers are satisfied with most of the services offered by the company. It was also observed that the customers demonstrated a lot of satisfaction referring to the kind of ordering, invoice service and payment. However, the clients consider the attendance service as being the most important feature of the company. Based on these results, a model to the management of the services of physical distribution based on the six sigma strategy was proposed with the purpose of guaranteeing the quality of services offered.